PHYSICIAN AS A MANAGER: PERSONAL AND MANAGERIAL CHARCTERISTICS, SAUDI ARABIA - A Mohamed, Badreldin; S ElNaif, Mohamed; A Al-hamdan, Adel; A Saeed, Abdallah; A, Ranyah; Orsud, Merdi Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 6 عدد 2 (2010), 2010)
BACKGROUND: The emergence of physicians' roles in key adminstrative positions within many King Saudi Arabia health care organizations has represented a major change in the medical profession over the last two decades. This have created a need for physicians who are willing to assume a high level of responsibility for managing evovling health care organizations. The study explores the perception of physician managers regarding their work, personal and managerial characteristics. METHODS: The data for this study were obtained from a sample of 200 physicians working in management positions in different health care organizations in Riyadh. Physicians were selected at random with probability proportional to size from a list containing managers in all health care organization to participate in the study RESULTS: Our results indicated that physician managers lack admistration skills. No formal training in medical adminstration and management because management principles are not integrated in the medical context and the majority were experienced in management for less than four years.  Very few possess the technical comptencies such as strategic planning, financial and economics knowledge. Boredom with medical practice, improvement of personal position and encouragement from others are related to being older, having more years in medicine and interest in medicine is reduced. The finding also supported the notion that physician manager can maintain stable levels of loyality to professional interest and organization. This dual commitment is related to work-relate characteristics involving sharing his time favorably to management job and to patient care. Recommendation: To improve their management skills physicians can benefit from mamagement education programs such as those offered by King Saud University.